Seasonal Variation in Population Dynamics of Helminth Parasites in Clarias batrachus from Natural wetlands of Sylhet, Bangladesh (International Journal of Natural Sciences, 2016)
A year round field investigations were conducted with the aim to examine the seasonal variation in population dynamics of helminth parasites in Clarias batrachus from different natural aquatic habitat of north-eastern region of Bangladesh, Sylhet. This article summarizes the percentage of prevalence, mean intensity, abundance and index of infestation of helminth parasites in the C. batrachus during different months and seasons of the year in accordance with temperature, humidity and rainfall. The investigation period were categorized into four seasons i.e. pre-monsoon (February-April), monsoon (May-July), post-monsoon (August- October) and winter (November- January). A total 180 C. batrachus host individuals were examined and among them 139 (67.87%) specimens were found to be infested with 2205 individuals of parasites of three different groups namely trematode, cestode and nematode. Almost (100%) prevalence of helminth infestation were recorded from both male and female C. batrachus during the winter (Nov-Jan), followed by (Feb-April) pre-monsoon (66.67-86.67%) and (Aug-Sep) post-monsoon (66.67-80.00%) while lowest (53.33-60.00%) in monsoon or rainy season (May-July). Lower range of environmental temperature (21.0525.050C), associated with moderate humidity (62.00-64.00%) and scarcity of rainfall increases the intensity of helminthes parasitic infestation in C. batrachus. In consistent to this, with the gradual increasing in ambient temperature (28.01- 30.010C) and humidity (75.00-89.00%) associated with moderate rainfall (33.40-790.90 mm) declining the intensity of helminthes infestation in C. batrachus of the study area.International Journal of Natural Sciences (2015), 5(2) 86-89